PHOSPHOLIPASE A 2 PLASMA ELASTASE ACTIVITY IN PRE AND POST PARTUM OF PRE-ECLAMPTIC WOMEN - Dayanand CD; Bambrana, Vanishree; Sr, Sheela (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objectives of the present study were to evaluate the activity of phospholipase A 2 , plasma elastase enzymes and to assess relation with an inflammatory marker high sensitive C-reactive protein (hs-CRP) in nonpregnant before and after delivery of normotensive pregnant and preeclamptic women. Methods: The study population consists of three groups: Nonpregnant (Group 1, n=57), normotensive pregnant (Group 2, n=57), and pre-eclamptic women (Group 3, n=57). Groups 2 and 3 were followed after delivery within 48 hrs. Phospholipase A , plasma elastase, and hs-CRP levels were determined spectrophotometrically. Results: The plasma elastase, phospholipase A 22 activity, and hs-CRP were elevated in pre-eclampsia significantly (p<0.05), nonsignificant rise in normotensive pregnant before delivery condition compared to nonpregnant women. However, plasma elastase in normal pregnancy and pre-eclampsia were decreased by 1.2- and 2.07-fold, respectively, after delivery. Whereas phospholipase A and hs-CRP found to be nonsignificantly decreased in the postdelivery status of the both the groups. Receiver operating characteristics curve analysis showed that elastase enzyme has diagnostic importance to assess inflammation on the basis of area under curve (0.758).2 Conclusion: Our research findings generated knowledge about raised level of plasma elastase enzyme by neutrophil degranulation represents inflammation in pre-eclampsia. Elevated elastase, phospholipase A Keywords: Elastase, High sensitive C - reactive protein, Phospholipase A2 with hs-CRP in pre-eclampsia serves as indicators of inflammation., Pre-eclampsia. <!–[endif]–><!–[if !mso]–> <!–[endif]–> 2 <!–[if !mso]–> <!–[endif]–><!–[if !mso & !vml]–>Â <!–[endif]–><!–[if !vml]–> <!–[if gte vml 1]> <v:shape id="_x0000_s1028" type="#_x0000_t202" style=’position:absolute; left:0;text-align:left;margin-left:375.9pt;margin-top:10.35pt;width:2.6pt; height:4.65pt;z-index:-6;mso-position-horizontal-relative:page’ filled="f" stroked="f"> <![endif]–><!–[if !vml]–><!–[endif]–>Objective:Theobjectivesofthepresentstudywere toevaluatetheactivityofphospholipaseA,plasmaelastaseenzymesand toassessrelationwith an inflammatorymarkerhighsensitiveC-reactiveprotein(hs-CRP)innonpregnantbeforeandafterdeliveryofnormotensivepregnantandpre- eclamptic women. Â <!–[endif]–><!–[if !mso]–> <!–[endif]–> 2 <!–[if !mso]–> <!–[endif]–><!–[if !mso & !vml]–>Â <!–[endif]–><!–[if !vml]–> <!–[if gte vml 1]><v:shape id="_x0000_s1029" type="#_x0000_t202" style=’position:absolute;left:0;text-align:left;margin-left:411.8pt; margin-top:19.6pt;width:2.6pt;height:4.65pt;z-index:-5; mso-position-horizontal-relative:page’ filled="f" stroked="f"> <![endif]–><!–[if !vml]–><!–[endif]–>Methods:Thestudypopulationconsistsofthreegroups:Nonpregnant(Group1,n=57),normotensivepregnant(Group2,n=57),andpre-eclamptic women(Group3,n=57).Groups2and3werefollowedafterdeliverywithin48hrs.PhospholipaseA,plasmaelastase,andhs-CRPlevelswere determined spectrophotometrically. <span style="font-size: 8.0pt; font-family: ’Cambria’,’serif’; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> <!–[endif]–><!–[if !mso]–> <!–[endif]–> 2 <!–[if !mso]–> <!–[endif]–><!–[if !mso & !vml]–>Â <!–[endif]–><!–[if !vml]–> <!–[if gte vml 1]><v:shape id="_x0000_s1033" type="#_x0000_t202" style=’position:absolute;left:0;text-align:left; margin-left:219.1pt;margin-top:15.35pt;width:2.6pt;height:4.65pt;z-index:-1; mso-position-horizontal-relative:page’ filled="f" stroked="f"> <![endif]–><!–[if !vml]–><!–[endif]–>Results:Theplasmaelastase,phospholipaseA Â activity,andhs-CRPwereelevatedinpre-eclampsiasignificantly(p<0.05),nonsignificantrisein <span style="font-size: 8.0pt; font-family: ’Cambria’,’serif’; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> normotensivepregnantbeforedeliveryconditioncomparedtononpregnantwomen.However,plasmaelastaseinnormalpregnancyandpre-eclampsia <!–[endif]–><!–[if !mso]–> <!–[endif]–> 2 <!–[if !mso]–> <!–[endif]–><!–[if !mso & !vml]–>Â <!–[endif]–><!–[if !vml]–> <!–[if gte vml 1]><v:shape id="_x0000_s1030" type="#_x0000_t202" style=’position:absolute;left:0;text-align:left;margin-left:362.95pt; margin-top:7.1pt;width:2.6pt;height:4.65pt;z-index:-4; mso-position-horizontal-relative:page’ filled="f" stroked="f"> <![endif]–><!–[if !vml]–><!–[endif]–>weredecreasedby1.2-and2.07-fold,respectively,afterdelivery.WhereasphospholipaseA Â andhs-CRPfoundtobenonsignificantlydecreasedinthe postdelivery status of the both the groups. Receiver operating characteristics curve analysis showed that elastase enzyme has diagnostic importance to assess inflammation on the basis of area under curve (0.758). Â <!–[endif]–><!–[if !mso]–> <!–[endif]–> 2 <!–[if !mso]–> <!–[endif]–><!–[if !mso & !vml]–>Â <!–[endif]–><!–[if !vml]–> <!–[if gte vml 1]><v:shape id="_x0000_s1031" type="#_x0000_t202" style=’position:absolute;left:0; text-align:left;margin-left:281.7pt;margin-top:19.6pt;width:2.6pt;height:4.65pt; z-index:-3;mso-position-horizontal-relative:page’ filled="f" stroked="f"> <![endif]–><!–[if !vml]–><!–[endif]–>Conclusion: Ourresearchfindingsgeneratedknowledgeaboutraisedlevelofplasmaelastaseenzymebyneutrophildegranulationrepresents inflammation in pre-eclampsia. Elevated elastase, phospholipase A Â with hs-CRP in pre-eclampsia serves as indicators of inflammation. <!–[if gte vml 1]> <v:shape id="_x0000_s1027" style=’position:absolute;left:1106;top:453;width:10083; height:0’ coordorigin="1106,453" coordsize="10083,0" path="m1106,453r10083,e" filled="f" strokecolor="#363435" strokeweight="2.5pt"> <![endif]–><!–[if !vml]–> <!–[endif]–><!–[if gte vml 1]> <![endif]–><!–[if !vml]–> <!–[endif]–><!–[if !mso]–> <!–[endif]–> 2 <!–[if !mso]–> <!–[endif]–><!–[if !mso & !vml]–>Â <!–[endif]–><!–[if !vml]–> <!–[endif]–><span style="font-size: 8.0pt; font-family: ’Meiryo’,’sans-serif’; color: #363435; letter-spacing: -.15pt; mso-font-width: 86%; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Keywords:<span style="font-size: 8.0pt; font-family: ’Cambria’,’serif’; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; color: #363435; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Elastase, High sensitive C - reactive protein, Phospholipase A, Pre-eclampsia.